2008
DOI: 10.1210/jc.2007-2768
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of the Rate and Extent of Spermatogenic Suppression during Hormonal Male Contraception: An Integrated Analysis

Abstract: Male hormonal contraceptives can be practically applied to a wide range of men but require coadministration of an androgen with a second agent (i.e. progestin) for earlier and more complete suppression of sperm output. Whereas considerable progress has been made toward defining clinically effective combinations, further optimization of androgen-progestin treatment regimens is still required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
92
0
3

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(100 citation statements)
references
References 67 publications
5
92
0
3
Order By: Relevance
“…In this analysis, we showed that the independent factors which most strongly influence the odds of eventual suppression are ethnicity and the use of a progestin as part of the treatment regimen (Table 1). 27 This is illustrated by actual suppression Ethnicity and male contraception N Ilani et al 580 rates observed in 1756 men treated with various male hormonal contraceptive regimens (Figure 1, using data from Ref. 27), which clearly shows that: (i) only up to 80% of Caucasian men suppress sperm output to ,10 6 ml 21 when received treatments that contain only androgens; (ii) up to 90% of East Asian men will adequately suppress sperm output when treated only with androgens; ( iii) the addition of a progestin increases to over 90% the proportion of Caucasian men who eventually suppress sperm output to ,10 6 ml 21 .…”
Section: Suppression Of Spermatogenesis: Adding a Progestin Overcomesmentioning
confidence: 99%
See 4 more Smart Citations
“…In this analysis, we showed that the independent factors which most strongly influence the odds of eventual suppression are ethnicity and the use of a progestin as part of the treatment regimen (Table 1). 27 This is illustrated by actual suppression Ethnicity and male contraception N Ilani et al 580 rates observed in 1756 men treated with various male hormonal contraceptive regimens (Figure 1, using data from Ref. 27), which clearly shows that: (i) only up to 80% of Caucasian men suppress sperm output to ,10 6 ml 21 when received treatments that contain only androgens; (ii) up to 90% of East Asian men will adequately suppress sperm output when treated only with androgens; ( iii) the addition of a progestin increases to over 90% the proportion of Caucasian men who eventually suppress sperm output to ,10 6 ml 21 .…”
Section: Suppression Of Spermatogenesis: Adding a Progestin Overcomesmentioning
confidence: 99%
“…27 This is illustrated by actual suppression Ethnicity and male contraception N Ilani et al 580 rates observed in 1756 men treated with various male hormonal contraceptive regimens (Figure 1, using data from Ref. 27), which clearly shows that: (i) only up to 80% of Caucasian men suppress sperm output to ,10 6 ml 21 when received treatments that contain only androgens; (ii) up to 90% of East Asian men will adequately suppress sperm output when treated only with androgens; ( iii) the addition of a progestin increases to over 90% the proportion of Caucasian men who eventually suppress sperm output to ,10 6 ml 21 . This proportion exceeds that observed by East Asian men treated with androgens alone; and (iv) nearly all East Asian men treated with androgen-progestin male hormonal contraceptive will eventually suppress sperm output to ,10 6 ml 21 .…”
Section: Suppression Of Spermatogenesis: Adding a Progestin Overcomesmentioning
confidence: 99%
See 3 more Smart Citations